P058 The mediating effect of sleep on the relationship between precarious employment and mental health. (9th November 2022) - Jaydarifard, S; Smith, S; Mann, D; Rossa, K; Huda, M; Nikooharf Salehi, E; Shekari Soleimanloo, S
Abstract: Introduction: Precarious work is characterised with high job insecurity, low income, and reduced rights and social protections. Current evidence suggests that precarious work is a risk factor for poor mental health. The relationship between these factors, and especially the contributing role of sleep may play in poor outcomes from precarious work, is unknown. This study investigated the mediating effects of sleep quality and duration on the relationship between precarious employment and poor mental health. Methods: Data were obtained from the Household, Income and Labour Dynamics in Australia (HILDA) survey (2017). A novel precarious employment score (PES) was developed capturing precarity across the following dimensions: Employment insecurity, level of income, and rights and social protections. Self-reported sleep quality and 24-hour sleep duration were included as mediators. Mediation analyses were conducted to evaluate the mediating effect of sleep duration and sleep quality on the relationship between precarious employment and mental health (SF-36 mental health subscale), after controlling for several covariates. Results: The PES identified 1446 (female, n=839) workers in precarious and 7922 (female, n=3949) non-precarious employees out of 9368. There was no significant direct association between precarious employment and mental health (P=.53). We observed no significant changes due to sleep quality in the association between precarious employment and mental health (Coefficient=-0.003, 95% CI: -0.01-0.00, P=0.32). However, this association was significant when considering sleep duration (Coefficient=0.34, 95% CI: 0.25-0.43, P<0.001). Discussion: Encouraging precarious employees to prioritise and promote sleep appropriately may promote well-being. Further objective measurement of sleep is warranted in this group.